China : Water Pricing and Water User Associations Sustainability - World Bank (Washington, DC, 2014)
Improved irrigation water pricing sufficient to cover Operation and Maintenance (O&M) and management costs for end-canal irrigation or tertiary facilities is a vital requirement for efficient irrigation service delivery and for sustainability of Water User Associations (WUAs). This study investigates the key aspects of end canal water pricing for irrigation, including the composition of the water fee, water price determination, water fee collection, and water fee management. The aim of the study is to provide specific reference and guidance for policy making on irrigation water pricing and on related strengthening of farmer WUAs for better end-canal O&M. Based on the literature reviewed for China, this is the first study of its kind which is designed to support policy making on end canal water fee reform, and simultaneously to address both end-canal water pricing and WUA development in that context. The study focuses on water fees for end- canal or tertiary water facilities in Chinese Irrigation Districts (IDs).